2004
DOI: 10.1086/421437
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Four New Massive and Dense Cold Cores

Abstract: We report the identification, from a 1.2 mm dust continuum emission survey toward massive star-forming regions, of four strong 1.2 mm sources without counterparts at mid-infrared (Midcourse Space Experiment [MSX ]) and far-infrared (IRAS) wavelengths. They have radii in the range 0.2-0.3 pc, dust temperatures 17 K, masses in the range 4 ; 10 2 2 ; 10 3 M , and densities of $2 ; 10 5 cm À3. We suggest that these objects are massive and dense cold cores that will eventually collapse to form high-mass stars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 25 publications
5
115
0
Order By: Relevance
“…We assess their potential contamination of the sample of the youngest massive clumps by using sensitive radio-surveys such as COR-NISH (Hoare et al 2012;Purcell et al 2013) and Urquhart et al (2007) to search for ionising emission from stars in our sample of types later than B0.5. Since there is no homogeneous high angular-resolution radio dataset available covering the en- (Garay et al 2004) with a positional shift between the dust and the 24 µm point source in the MIPSGAL image, which also coincides with a UC-H II region from CORNISH marked by a blue cross.…”
Section: Tracers Of Embedded High-mass Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assess their potential contamination of the sample of the youngest massive clumps by using sensitive radio-surveys such as COR-NISH (Hoare et al 2012;Purcell et al 2013) and Urquhart et al (2007) to search for ionising emission from stars in our sample of types later than B0.5. Since there is no homogeneous high angular-resolution radio dataset available covering the en- (Garay et al 2004) with a positional shift between the dust and the 24 µm point source in the MIPSGAL image, which also coincides with a UC-H II region from CORNISH marked by a blue cross.…”
Section: Tracers Of Embedded High-mass Starsmentioning
confidence: 99%
“…Garay et al 2004;Thompson et al 2005). To look for neighbouring, more evolved objects with UC-H II regions in the close vicinity of the infrared-quiet sample, we used the CS (2-1) survey of IRAS sources (Bronfman et al 1996), which is complete towards IRAS selected UC-H II regions in the Galactic plane.…”
Section: Massive Cluster Progenitors In Isolation?mentioning
confidence: 99%
“…Much effort has focused on follow-up studies of bright IR sources detected by the Infrared Astronomy Satellite (IRAS) and showing far-infrared (FIR) colors typical of ultra-compact H ii regions (Wood & Churchwell 1989), e.g., in high-density molecular tracers (Bronfman et al 1996;Molinari et al 1996), dust continuum emission , or maser emission (e.g., Palla et al 1993;Beuther et al 2002). While some studies have revealed a few massive cold cores in the neighborhood of the central compact H ii region (e.g., Garay et al 2004), they were mostly biased against the earliest, possibly coldest phases of massive star formation.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…Infrared studies, however, cannot provide a complete census of the birth sites of massive stars, since there are massive condensations that are undetected at infrared wavelengths. For example, Garay et al (2004) found four clumps with masses between 4 × 10 2 and 2 × 10 3 M and densities of ∼2 × 10 5 cm −3 , without infrared emission, located close to clumps associated with MSFRs. They suggested that these cold ( 17 K), dense, and massive clumps will eventually form high mass stars.…”
Section: Massive-star Forming Regionsmentioning
confidence: 99%